ANALISIS CACAT PENYUSUTAN DAN NILAI KEKERASAN PRODUK COR ALUMINIUM SKRAP DENGAN VARIASI UKURAN MILD STEEL CYLINDER MOLD - Nurhabibah Paramitha Eka Utami; Pratiwi, Diah Kusuma; Chandra, Hendri; Ellyanie, Ellyanie; Gustini, Gustini; Astuti, Astuti (Universitas Sriwijaya, 2025)
The research was conducted to investigate the effect of mold diameter variation on the hardness and shrinkage of cast products made from aluminum scrap. Three mold diameter variations were used in the casting process: 50 mm, 70 mm, and 100 mm. The testing methods included shrinkage measurement, Brinell hardness testing, and dye penetrant inspection. The test results showed that the 50 mm sample had the highest hardness value of 52.09 BHN and the lowest shrinkage defect of 25.25%, while the 100 mm diameter sample exhibited the lowest hardness value of 48.72 BHN and the highest shrinkage defect of 28%. This phenomenon occurred due to differences in cooling rates during the solidification process, where larger mold diameters experienced slower cooling, resulting in coarser microstructure grains and a higher occurrence of shrinkage defects.